Performance analysis of dual-frequency range estimation methods in the presence of ionospheric and multipath propagation effects - Jie Zhang; Skournetou, D.; Lohan, E.; Wei Wang; Sand, S. (2012 International Conference on Localization and GNSS, 2012)
In the global navigation satellite systems (GNSS), the performance of GNSS is subject to various errors, such as ionosphere delay, receiver noise and multipath. Among all these errors, the ionosphere delay error and multipath error are commonly regarded as the most limiting factors. In theory, a dual-frequency receiver can eliminate the ionospheric effect. However, in reality, the tracking error has effects on the ionospheric delay correction. This effect has not been studied, especially in realistic channel scenarios. In this paper, the authors investigate the effect of tracking error, obtained from Galileo signal Simulink-based simulators with realistic channel models on the range estimation in dual frequency receivers and compare the performance of three dual frequency ionosphere delay correction methods, namely the least square (LS), constrained LS (CLS) and Bruce Force Constraint (BFC). The results showed that the BFC performed the best below a fairly high ionosphere delay error. The LS method was only affected by multipath error, but the effect was small. CLS performance was better than or equal to LS at the expense of increased complexity.